2016
DOI: 10.1364/oe.24.030411
|View full text |Cite
|
Sign up to set email alerts
|

All-optical tuning of EIT-like dielectric metasurfaces by means of chalcogenide phase change materials

Abstract: Electromagnetically induced transparency (EIT) is a pump-induced narrowband transparency window within an absorption line of the probe beam spectrum in an atomic system. In this paper we propose a way to bring together the all-dielectric metamaterials to have EIT-like effects and to optically tune the response by hybridizing them with a layer of a phase change material. We propose a design of the metamaterial based on Si nanoresonators that can support an EIT-like resonant response. On the top of the resonator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…PAS can therefore directly characterize the spectral position and the efficiency of the modes. For a specific application, one can optimize the geometric parameters, e.g., by using methods in [38] or [39]. One of the subjects of ongoing work is the use of the resonant modes for chiral near field formation.…”
Section: Resultsmentioning
confidence: 99%
“…PAS can therefore directly characterize the spectral position and the efficiency of the modes. For a specific application, one can optimize the geometric parameters, e.g., by using methods in [38] or [39]. One of the subjects of ongoing work is the use of the resonant modes for chiral near field formation.…”
Section: Resultsmentioning
confidence: 99%
“…60 Particularly, a few works have numerically illustrated that the chalcogenide metasurfaces may lead to tunable EIT. [61][62][63] Following these theoretical predictions, the concept of tunable EIT was experimentally verified in a very recent work, which showed that a chalcogenide metasurface can be used to obtain a nonreversible switching of EIT via a thermal annealing system. 64 These previous works showed the promising potential of chalcogenide PCM in reconfigurable EIT metadevices in the optical region.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, new strategies in view of the EIT or Fano resonances based on all-dielectric metasurfaces were introduced to restrain these losses, which have exhibited great possibility of producing high Q-factor resonances [16]- [32]. A common feature of the EIT-like all-dielectric metasurface demonstrated so far is dependent on multiple interacted structures within the unit cell, such as orthogonal silicon bars [25]- [27], silicon-based bar-ring resonator [28]- [30]. Generally in these resonator systems, one structure is designed to support the bright mode that can directly couple to the free space, the other one is served as a dark or trapped mode, which is less-accessible, or inaccessible from the incident optical field.…”
Section: Introductionmentioning
confidence: 99%